Tartrazine degradation by supported TiO2 on magnetic particles - Heredia, Carla Lorena (2015)
Magnetic beads were obtained by dropping a solution of sodium alginate containing magnetite particles into a CaCl2 solution. TiO2 anatase particles were synthetized by a sol-gel method at low temperature (75 °C), and were supported on magnetic beads to obtain the magnetic photocatalyst, MC. Magnetite particles and magnetic photocatalyst were characterized by nitrogen adsorption (BET, surface area), their morphology observed by scanning electronic microscopy (SEM) and TiO2 phase was analyzed by means of Raman spectroscopy. The photocatalytic activity of MC was evaluated on tartrazine degradation, highly used in food industry, at two different concentrations. Finally, MC stability was evaluated by reusability assays in several subsequent cycles. Results showed a good photocatalytic response for tartrazine degradation, especially at low concentration, easy recuperation and appropriate perform in the reusability of MC.